(untitled) - Clark, Carol Higgins (New York, 2008)
Sent to Branson, Missouri, to protect Brigid, a singer whose life has been threatened, sleuth Regan Reilly follows her client to Ireland, where Brigid is to give a concert and where Regan must foil a murderer’s diabolical schemes.
Keywords: Private investigators,Women detectives,Điều tra thông tin,Nữ thám tử; Fiction,Fiction,Tiểu thuyết,Tiểu thuyết